Educating Children based on Values of Sunda: Islamic Perspective - Nurjanah, Nunuy; Srihilmawati, Rostika; Handrianto, Ciptro; Rahman, M Arinal (Islamic Research, 2023)
Cultural elements, such as proverbs, hold deeply rooted educational values that have been integral to shaping societal norms and practices. These values can be utilized to educate children and build their character from an early age, whether through formal or nonformal education, guided by parents or teachers. In Islamic education, the integration of cultural values has been extensively studied and discussed. This study aims to explore how the values embedded in Sundanese culture can serve as a foundation for educating children from an Islamic perspective. Through a qualitative approach, the research examines Sundanese proverbs and their alignment with Islamic educational principles, focusing on the roles of parents, teachers, and educational institutions in characterbuilding. The study finds that educating children based on Sundanese values within an Islamic framework requires a comprehensive understanding of both cultural and religious teachings. A key element is the pivotal role of mothers as primary role models, supported by teachers and schools, to nurture children who are devoted to Allah and possess noble character. This research highlights the importance of integrating Sundanese cultural values with Islamic educational principles to create a holistic approach to character education. It underscores the collaborative roles of family, educators, and society in fostering a generation rooted in cultural wisdom and Islamic ethics.